IDENTIFIKASI DAN PENILAIAN OBYEK DAYA TARIK WISATA ALAM (Studi Kasus di Taman Nasional Ujung Kulon) - rani, Utara Koma; Satjapradja, Ombo Satjapradja; Salampessy, Messalina L (Jurnal Nusa Sylva, 2015)
Ujung Kulon National Park has a wide variety of natural tourist different and nice. However, this potential has not been identified by either. For this tourism potential need to be identified and assessment as an effort to develop this location. This research id aimed to identify the potential of nature tourism and assess of object natural tourist attraction at this conservation area. The method used is a case study, in which data collection is done through in-depth interviewsÂ  and involved observation. Data were analyzed using assessment of object natural tourist attraction. The results showed that the potential of tourism in Gunung Tilu and Curug Cibayoni which has a high value rated with excellent criteria it needs to be included into the form of tourist activities in accordance with the assessment of Object Natural Tourist Attraction. Forms of nature tourism activities are educational tour; religious tour; recreation; tracking; set up a stall for society; agricultural education tour; and handicraft.